Characterization of fire vulnerable Pinus halepensis ecosystems in Spain and Greece - Kazanis D.; Gimeno T.; Pausas J.; Vallejo R.; Arianoutsou M. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
The knowledge of factors that govern a system's vulnerability permits the establishment of priority action zones immediately after a fire to mitigate its effects. An extensive survey of several burned areas in Spain and Greece has been arranged, in order to identify vulnerable patches in terms of low vegetation cover and low pine regeneration. After visually identifying the patches, a database has been elaborated, including the most relevant information. A combination of factors related to bedrock, slope, aspect, soil stoniness and forest type were found to be associated with the poorest vegetation recovery. Furthermore, the crucial role of short fire interval was established. In order to obtain an early, short-term characterization of the vulnerable patches, vegetation structure had been analysed no later than two years after the last fire event. In both regions vegetation cover and pine sapling density was less than expected from reference data. The tendency seems to be towards the formation of shrublands instead of woodlands with increased levels of erosion risk.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)